Metal vapor synthesis of ultrasmall Pd nanoparticles functionalized with N-heterocyclic carbenes. Issue 36 (16th August 2018) - Tegeder, Patricia; Marelli, Marcello; Freitag, Matthias; Polito, Laura; Lamping, Sebastian; Psaro, Rinaldo; Glorius, Frank; Ravoo, Bart Jan; Evangelisti, Claudio
Abstract : The synthesis of N-heterocyclic carbene (NHC)-stabilized palladium nanoparticles (PdNPs) by an entirely new strategy comprising the NHC functionalization of ligand-free PdNPs obtained by metal vapor synthesis is described. Abstract : The synthesis of N-heterocyclic carbene (NHC)-stabilized palladium nanoparticles (PdNPs) by an entirely new strategy comprising the NHC functionalization of ligand-free PdNPs obtained by metal vapor synthesis is described. Detailed characterization confirms the formation of very small monodisperse PdNPs (2.3 nm) and the presence of the NHC ligand on the Pd surface. The stable NHC-functionalized PdNPs dispersed onto a carbon support showed high activity in the hydrogenation of limonene with enhanced regioselectivity in comparison to bare PdNPs on carbon.